Electrochemical DNA biosensor for the detection of infectious bronchitis virus using a multi-walled carbon nanotube-modified gold electrode - Md Safiul Alam Bhuiyan; Gilbert Ringgit; Subir Sarker; Ag Muhammad Sagaf Abu Bakar; Suryani Saallah; Zarina Amin; Sharifudin Md. Shaarani; Shafiquzzaman Siddiquee (MDPI, 2025)
Infectious bronchitis virus (IBV) is an enveloped, positive-sense, single-stranded RNA virus belonging to the genus Gammacoronavirus. It primarily infects avian species, causing respiratory and renal disease and irreversible damage to the oviduct, which can lead to high mortality rates in chickens. The lack of rapid and reliable diagnostic tools for on-farm IBV detection hampers timely disease management and control measures. The introduction of DNA biosensors offers a promising approach for the sensitive and specific detection of IBV, facilitating rapid identification and intervention. In this study, an electrochemical DNA biosensor with a multi-walled carbon nanotube (MWCNT)-modified gold electrode was developed for IBV detection. The biosensor targeted the target-specific 5 ′ untranslated region (5′ -UTR) of the IBV genome. Under optimal conditions, the immobilization and hybridization efficiencies were evaluated by cyclic voltammetry (CV) and differential pulse voltammetry (DPV), with methylene blue as a redox indicator. The developed DNA biosensor demonstrated a dynamic detection range from 2.0 × 10−12 to 2.0 × 10−5 mol L−1 , with a limit of detection (LOD) of 2.6 nM and a limit of quantification (LOQ) of 0.79 nM. Validation using a small subset of clinical samples, including crude complementary DNA, and polymerase chain reaction products, showed high recovery rates ranging from 95.41% to 99.55%. While these findings highlight the potential of the proposed DNA biosensor as an innovative diagnostic tool for IBV detection, this study remains a proof of concept. However, further validation using a large number of clinical samples is essential to assess its feasibility, robustness, and practical application in a real-world farm setting.